Modification of tooth development by heat shock protein 60 - Papp, Tamas (Int J Oral Sci, 2016)
Although several heat shock proteins have been investigated in relation to tooth development, no available information is available about the spatial and temporal expression pattern of heat shock protein 60 (Hsp 60). To characterize Hsp 60 expression in the structures of the developing tooth germ, we used Western blotting, immunohistochemistry and in situ hybridization. Hsp 60 was present in high amounts in the inner and outer enamel epithelia, enamel knot (EK) and stratum intermedium (SI). Hsp 60 also appeared in odontoblasts beginning in the bell stage. To obtain data on the possible effect of Hsp 60 on isolated lower incisors from mice, we performed in vitro culturing. To investigate the effect of exogenous Hsp 60 on the cell cycle during culturing, we used the 5-bromo-2-deoxyuridine (BrdU) incorporation test on dental cells. Exogenously administered Hsp 60 caused bluntness at the apical part of the 16.5-day-old tooth germs, but it did not influence the proliferation rate of dental cells. We identified the expression of Hsp 60 in the developing tooth germ, which was present in high concentrations in the inner and outer enamel epithelia, EK, SI and odontoblasts. High concentration of exogenous Hsp 60 can cause abnormal morphology of the tooth germ, but it did not influence the proliferation rate of the dental cells. Our results suggest that increased levels of Hsp 60 may cause abnormalities in the morphological development of the tooth germ and support the data on the significance of Hsp during the developmental processes.